The clinical effects of sodium hyaluronate, polyethylene glycol, and dextran-70 eye drops in relieving dry eye after phacoemulsification. Issue 25 (25th June 2021) - Duan, Zhi-Hui; Tang, Yi-Fei
Abstract : Abstract: To compare the clinical efficacy of sodium hyaluronate eye drops, polyethylene glycol eye drops, and compound dextran eye drops in the treatment of dry eye after phacoemulsification of cataract. A total of 99 patients with dry eye after cataract phacoemulsification combined with intraocular lens implantation were treated in our hospital. Patients were divided into group A (sodium hyaluronate eye drops), group B (polyethylene glycol eye drops), and group C (dextran-70 eye drops). The clinical effect, tear film breakup time, basic tear secretion, corneal staining score, dry eye symptom score, and the incidence of ocular irritation were assessed. On the 3rd, 15th, 30th, and 60th day after operation, the tear film breakup time, corneal staining score, Schirmer I test, and dry eye symptom score in group A and group B were better than those in group C ( P < .05). In addition, there were no significant differences in tear breakdown time, corneal staining score, Schirmer I test, and dry eye symptom score between group A and group B ( P > .05). At 3 days to 60 days after operation, the incidence of dry eye in group A (12.12%) and group B (18.18%) was lower than that in group C (39.39%), and the incidence of dry eye in group A was significantly lower than that in group B ( P < .05). The effect of sodium hyaluronate eye drops elicited a greater beneficial impact as compared to polyethylene glycol eye drops and dextran-70 eye drops.